2015
DOI: 10.1186/s13014-015-0421-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for asymptomatic brain metastasis in epidermal growth factor receptor mutant non-small cell lung cancer without prior tyrosine kinase inhibitors treatment: a retrospective clinical study

Abstract: BackgroundNon-small cell lung cancer (NSCLC) with brain metastasis (BM) harboring an epidermal growth factor receptor (EGFR) mutation shows good response to tyrosine kinase inhibitors (TKIs). This study is to assess the appropriate timing of brain radiotherapy (RT) for asymptomatic BM in EGFR mutant NSCLC patients.MethodsThere were 628 patients diagnosed with EGFR mutant NSCLC between October 2005 and December 2011. Treatment outcomes had been retrospectively evaluated in 96 patients with asymptomatic BM witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…The factors including gender, age, radiotherapy dose in whole brain and pathological grading have no significant influence on survival. The ECOG score is higher, the poorer the prognosis will be, which is to correspondence with the previous reports [26][27][28]. The radiotherapy dose in intracranial metastases is positively related with the prognosis.…”
Section: It Is Recommended By National Comprehensive Cancersupporting
confidence: 78%
“…The factors including gender, age, radiotherapy dose in whole brain and pathological grading have no significant influence on survival. The ECOG score is higher, the poorer the prognosis will be, which is to correspondence with the previous reports [26][27][28]. The radiotherapy dose in intracranial metastases is positively related with the prognosis.…”
Section: It Is Recommended By National Comprehensive Cancersupporting
confidence: 78%
“…In fact, small, asymptomatic brain metastases respond well to TKI treatment alone in treatment naïve patients [29]. Liu et al [29] analyzed overall survival in 96 neurologically-asymptomatic, EGFR-mutant NCSLC patients with brain metastases under three treatment groups: upfront radiation therapy (RT, both WBRT and SRS), delayed RT but upfront TKI treatment, or no RT. They argued for upfront EGFR-TKI followed by RT when appropriate as they found no significant impact on OS with delayed RT.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25–30% of NSCLC patients experience CNS metastases [20]. EGFR TKIs have become a first-line treatment for EGFR mutation-positive NSCLC patients; they are also used in NSCLC patients with brain metastases, and numerous studies have confirmed their safety and efficacy [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Different from research exploring the mechanism of tumor transplantation and blood metastases as the object of study, this study primarily compared the efficacy of EGFR-TKIs in the treatment of intracranial tumors, for which the direct intracranial transplant method created a more consistent model. Furthermore, whether in drug efficacy studies of metastatic brain tumors or intracranial primary tumors, this type of animal model is widely applied [20, 42, 43]. Secondly, in this study, we did not investigate the potential effect of WBRT on the penetration of EGFR-TKIs into the CSF.…”
Section: Discussionmentioning
confidence: 99%